Accumulation of heavy particles in circular bounded vortex flows induced by two small rotating cylinders. (April 2019) - Ku, Xiaoke; Li, Heng; Lin, Jianzhong; Jin, Hanhui
Highlights: Motion of heavy particles in vortices induced by two rotating cylinders is studied. Five different particle accumulation patterns are identified. The critical values of the center-to-center distance are reported. More particles accumulate on the wall under two-way coupling. Abstract: In the present study, we adopt an Eulerian–Lagrangian CFD model based on the discrete element method (DEM) and immersed boundary method (IBM) to numerically investigate the accumulation behavior of heavy particles in circular bounded vortex flows induced by two small rotating cylinders. Both one-way and two-way couplings combined with the particle-particle and particle-wall collisions which are resolved by a hard-sphere approach are analyzed and effects of Stokes number, Reynolds number, the center-to-center distance between the circular domain and each small cylinder ( r 1 ) and particle number are also comprehensively explored. It is found that, under one-way coupling, there is always a stable state for the accumulation of particles trapped inside the circular domain. Moreover, five different particle accumulation patterns are identified as the two small rotating cylinders move away from the domain center and the critical values of r 1 are also reported. However, under two-way coupling, the motion of the particles is irregular and the stable closed trajectories or accumulation points appearing in cases under one-way coupling cease to exist, due to the intense interaction between particles and the gas phase. In addition, many more particles accumulate on the wall under two-way coupling than under one-way coupling at the same conditions, demonstrating that the influence of particles on the flow will in turn strongly affect the particle motion and push more particles to the wall. The percentage of particles accumulated on the wall increases with increasing Stokes number and Reynolds number, whereas it decreases as the center-to-center distance between the circular domain and each small rotating cylinder increases under both one-way and two-way couplings.